APPROACHES TO CONTROL SORGHUM RED STRIPE VIRUS - AND S. D. CHOUDHARI, T. B. GARUD, V. R. MAU, O. D. KOHIRE (Indian Phytopathology, 2002)
Out of 1985 germplasm lines screened, 47 were tolerant and 29 were resistant to sorghum red stripe virus. Sowing of sorghum crop 20 metres away from sugarcane plot and controlling the population of aphid by alternate spray of. endosulphan (0.05 per cent) and dimethoate (0.03 per cent) significantly (65 to 85 per cent) reduced the disease incidence.